Surface and electron structure of the 6H-SiC(0001)-(3×3) surface and ultrathin Ag films on Si(111) and Si(001): Тонкие пленки - Gasparov, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Surface topographic (LEED, STM) and spectroscopic (ARUPS, XPS, STS) studies have been performed on the Si-terminated 6H-SiC(0001)-(3×3) surface and Ag superstructures and ultrathin films on Si(001) and Si(111) surfaces, using a scanning tunneling microscope (STM) in ultrahigh vacuum. Our results confirm that a 2D epitaxial metal growth is favored on Si(001) at low temperatures and a solid, two-domain Ag(111) film has been achieved at coverage’s as low as 10 ML. We have found that the films reveal a morphology with 3-dimensionalfeatures and with well defined honeycomb structure in between. An atomically flat Si(111)/Ag-(√3̅×√3̅)R30° surface has been modified by use of a scanning tunneling microscope (STM) in ultrahigh vacuum (UHV). High quality 6H-SiC(0001)-(3×3) and Si(111)-Ag(√3̅×√3̅)R30° over structures have been prepared and studied by means of ARUPS, XPS and LEED. The local density of states proportional to the normalized differential conductivity (dI / dV )/(I / V ) vs V spectra show a distinct bands of empty (–0.6 eV) and filled (0.65 eV) sites separated by 1.2 eV, for both areas. The results support a Mott–Hubbard-type model as used for the calculation of the density of states of 6H-SiC(0001)-(3×3) surface with Hubbard gap 1 eV.